Solomon Islands Tourism : Investable Site Identification and Selection : A Guide To The Identification And Selection Of Land For Future Tourism Investment (Washington, DC, 2022)
A key ingredient for private sector investment in tourism is land. However, land has been identified by foreign investors as a key barrier to investing in Solomon Islands’ tourism sector. More specifically, two key land-related aspects have been pinpointed as investment barriers: i) limited investable land: there is a perception from investors that very little land, if any, is available for tourism development and ii) land tenure issues, including land disputes, which contribute to a high-risk investment profile for Solomon Islands.2 In response to these two key barriers, International Finance Corporation (IFC), in collaboration with Solomon Islands’ Ministry of Culture and Tourism (MCT), has developed this Guide to provide practical support to SIG investment teams on identifying, prioritizing and profiling investable sites for the purpose of tourism in Solomon Islands.